Formation of hollow nanoshells in solution-based reactions via collision coalescence of nanobubble–particle systems. (11th May 2016) - Vongehr, Sascha; Tang, Shaochun
Abstract: Research on hollow nanoshells has, for years, claimed to involve free, pre-existing nanobubbles as soft templates. It is a challenge to demonstrate this due to the difficulty of in situ observation during solution-based reactions. We show that no available free-bubble theory can describe the mysterious behavior of the bubble number density n . A new mechanism of collision coalescence of bubble–particle systems is suggested to form hollow nanoshells. By approximating relative velocity as ∼ R − z ( R is bubble radius), numerical simulations can reproduce the counterintuitive observations in the regime 1 < z < 2. We discuss the mechanism based on successful synthesis of grain-monolayer thin, fractal-like incomplete, multi-metallic nanoshells with superior catalytic activity. The behaviors of n, R, and shell thickness h are closely reproduced by z = 1.6.